Monitoring of Impacts of Offshore Platforms in the Adriatic Sea (Italy) - Trabucco, B.; Maggi, C.; Manfra, L.; Nonnis, O.; Mento, R. Di; Mannozzi, M.; Lamberti, C. Virno; Cicero, A. M.; Gabellini, M. (IntechOpen, 2012)
None